A decade of innovation and development. Issue 2 (2nd September 2021) - Joseph, K. J.; Cozzens, Susan; De Fuentes, Claudia; Dutrénit, Gabriela; Kruss, Glenda; Lema, Rasmus
ABSTRACT: This year marks the tenth anniversary of Innovation and Development . This special anniversary issue brings together a set of reflective articles by key scholars in our field. Each article contributes in a different way to advance the agenda on innovation and its relations to sustainable and inclusive development. Several of the papers take a step back and reflect on overall developments in the field, and in this way, propose future directions. In this introductory article, we recollect the journey of the journal, bring out the insights emerging from the anniversary issue and chart and an agenda for the future.